Rancang Bangun Sistem Informasi Manajemen Data Penerimaan Zakat, Infaq, Shodaqoh Berbasis Web - Dewi Puji Lestari; Budiman Budiman Budiman; Izzatul Umami (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2022)
Zakat, Infaq and Sadaqoh are forms of worship for Muslims to carry out the third pillar of Islam. The amil zakat, infaq and shodaqoh nahdlatul ulama (lazisnu) institutions in the village of Sepanyul Gudo in their management are still experiencing many problems because there are still many obstacles, especially the management of ZIS funds that enter and their distribution is often problematic because the incoming and outgoing data are not integrated. In addition, it can also disseminate information on the distribution of ZIS funds carried out during religious activities that are inefficient and disrupt these activities. With the description of the problems that occur, design a system that can help solve this by designing a web-based data management information system for zakat, infaq and shodaqoh recipients. The application is designed using the PHP and MySQL programming languages ​​as databases. System development using a Linear Sequential Model approach is accompanied by a design using UML (Unified Modeling Language) including use case diagrams, activity diagrams, and sequence diagrams. So as to produce a web-based online information system, so that people who will participate in ZIS can easily access it.